2017
DOI: 10.1108/sr-10-2016-0230
|View full text |Cite
|
Sign up to set email alerts
|

A review on recent advances of CNTs as gas sensors

Abstract: Purpose This review paper aims to focus on recent advances of carbon nanotubes (CNTs) to produce gas sensors. Gas sensors are widely used for monitoring hazardous gas leakages and emissions in the industry, households and other areas. For better safety and a healthy environment, it is highly desirable to have gas sensors with higher accuracy and enhanced sensing features. Design/methodology/approach In this review, the authors focus on recent contributions of CNTs to the technology for developing different t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(48 citation statements)
references
References 79 publications
4
41
0
Order By: Relevance
“…Moreover, there is a little difference in the results obtained in dry and humid environments, showing a very slight sensitivity to humidity. This result is in accordance with the theoretical studies [9], which predict a small sensitivity for water; this latter is also accompanied by a small charge transfer (which can be positive or negative depending on the tube chirality). In the tested material, water increases the conductivity, which indicates a negative charge transfer (acceptor behavior), in contrast with what happens with the most part of metal oxides.…”
Section: Study Of the Baseline Conductancesupporting
confidence: 92%
See 3 more Smart Citations
“…Moreover, there is a little difference in the results obtained in dry and humid environments, showing a very slight sensitivity to humidity. This result is in accordance with the theoretical studies [9], which predict a small sensitivity for water; this latter is also accompanied by a small charge transfer (which can be positive or negative depending on the tube chirality). In the tested material, water increases the conductivity, which indicates a negative charge transfer (acceptor behavior), in contrast with what happens with the most part of metal oxides.…”
Section: Study Of the Baseline Conductancesupporting
confidence: 92%
“…As expected, on the basis of previous experimental works and from theoretical studies [9], the response to NO 2 is the one observed in other p-type semiconductors in all the tested conditions. In detail, the adsorbed molecule behaves as an acceptor that, by trapping free electrons [9], creates additional holes available for the conduction, so that the exposure to NO 2 causes an increase of the tube conductivity.…”
Section: Study Of the Response To Nosupporting
confidence: 89%
See 2 more Smart Citations
“…Our interest in that area stems from the fact that carbon based nanomaterials, e.g. CNTs, [24][25][26] CNFs 27-30 and graphene 31,32 have proven to be effective alternatives to well-established metal oxide based gas sensors. Key features of these materials compared to metal oxides are operating temperatures as low as room temperature and an increased sensitivity and high versatility introduced by the ease of functionalization of these materials.…”
Section: Introductionmentioning
confidence: 99%